Implementasi Diversity Marketing pada Brand Kosmetik Lokal ‘Feyrely’ di Instagram - Kiranastari Asoka Sumantri; Cheryl Arshiefa Krisdanu (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Over the last few years, local Indonesian cosmetic brands have begun to raise diversity themes in their marketing strategies through social media; one of them is Feyrely. The social media platform used by Feyrely to communicate as part of its marketing strategy is Instagram. This journal aims to analyze whether Feyrely has reflected on the diversity aspects in their Instagram and described the aspects of diversity delivered. The analysis was done using the method of content analysis and interviews with representatives of Feyrely. In this study, the aspects of diversity that will be used to analyze the suitability of content with the concept of diversity are the second (internal) and third (external) layers of the model, because the representation of these aspects can be identified visually through photos/videos and Instagram captions. The results of the observations show that from the 16 aspects of diversity, Feyrely only displays aspects of age, physical ability, race, religion, and appearance. So Feyrely has not presented them widely. Most of the diversity aspects displayed are aspects of the second layer, racial diversity.